FORMATION OF MEAT PRODUCTIVITY AND BEEF QUALITY OF THE SIMMENTHAL CATTLE AND THEIR CROSSES WITH HEREFORD AND CHAROLAIS BULLS - Petrovich , Ivan; Lukyanov, Vladimir; Grikshas, Styapas; Kubatbekov, Tursumbai; Abdulmuslimov, Abdulmuslim; Feyzullaev, Feyzullah (Revista Inclusiones, 2020)
In the conditions of the State Scientific Establishment (SSE) Tula Research Institute of Agriculture of the RAAS, the productivity and quality of Simmental beef bull calves and their crosses with Hereford and Charolais breeds were studied from 2010 to 2016. Three groups of bull calves, 17 animals in each, were chosen and formed. The first group (reference) included purebred Simmental bull calves (S), the second and the third (experimental) groups contained the crossbred bull calves obtained by crossing the Simmental cows with the Hereford (S x H) and the Charolais (S x C) bulls, respectively. The calves were grown from birth to weaning at the age of six months using the Cow – Calf technology of beef cattle breeding. After weaning the young animals, the technology envisaged keeping them tied in the stalls. A check slaughtering was performed at the age of 6 and 18 months.